P‐143: The Investigation of Improvement Transmittance with PSVA LC Curing Method in Curved Design Structure. Issue 1 (30th May 2018) - Ren, Wei; Hsieh, Chung-Ching; Song, Yan-Jun; Zhao, Yong-Chao; Zhao, Ren-Tang; Li, Xiang; Zhang, Yu; Yuan, Chun-Ge; Yuan, Fu; Lin, His-Chien
Abstract : This work investigation a UV Curing mode and driving mode for PS‐VA transimittance analysis. At the Data BM less (DBS) design structure in curved LCD application and development, Afer voltage signal curing method, it impact LC pre‐tilt angle and dark line, transmittace in this paper. we build a module cell of LC alignment at the elecltic, this paper improving the optical perfornance at the DBS TFT Design, the best curing voltage signs fine tuning at this DBS TFT for Curved LCD